Threats to the Ideology of Pancasila In the Reform Era: Praxis Case of Regional Development Policy - BUDI GUNAWAN; BARITO MULYO RATMONO (Jurnal Studi Pemerintahan, 2018)
This study about the ideology of Pancasila in the praxis of development policy at Local Government (Pemda), and also identifies the potential threat to the existence of Pancasila ideology in the reform era. Through a selection of field study research methods combined with Focus Group Discussion (FGD), we want to know and analyse critically how big ideology operates in development policy praxis. This study identifies the symptoms of two potential threats to Pancasila ideology in the Kulonprogo region. First comes from the stronghold of global capitalism through agents that continue to expand the market, systematically proceeds strategically with the policies of the regional government. Both come from the stronghold of the global religious movement that carries the ideology of Islamic universalism against diversity, thus threatening the ideology of Pancasila, especially the precepts of Indonesian Unity. In the meantime to face the threat of religious radicalism, intelligence strategies can use multiple options. Starting from the conventional approach of exploiting internal conflicts within the radical organisation, cultural strategy by facilitating the occurrence of strategic alliances between traditional- cultural-cultural forces with the power of locality culture face the attacks of radical Islamic political movements based on anti-Pancasila.